Decomposition formulas for some quadruple hypergeometric series - Berdyshev, A.S.; Hasanov, A.; Ryskan, A.R. (KU Publ., 2020)
In the present work, the authors obtained operator identities and decomposition formulas for second order Gauss hypergeometric series of four variables into products containing simpler hypergeometric functions. A Choi–Hasanov method based on the inverse pairs of symbolic operators is used. The obtained expansion formulas for the hypergeometric functions of four variables will allow us to study the properties of these functions. These decompositions are used to study the solvability of boundary value problems for degenerate multidimensional partial differential equations.
Кейбір төрт айнымалы гипергеометриялық қатарлар үшін жіктеу формулалары
Формулы разложения для некоторых гипергеометрических рядов четырех переменных
Keywords: Appell hypergeometric function; Lauricella function; Saran function; Quadruple hypergeometric series; Decomposition formulas; Operator identities; Inverse symbolic operators